Modernity and terrorism : from anti-modernity to modern global terror - Zafirovski, Milan, 1958- (Studies in critical social sciences, 2013)
In Modernity and Terrorism Zafirovski and Rodeheaver analyze the nature, types, and causes of terrorism. The book redefines terrorism in novel comprehensive way, considers counter-state and state terrorism, and identifies and predicts conservative anti-modernity as the main cause of terrorism.